PENGARUH STRES AKADEMIK TERHADAP KESEJAHTERAAN PSIKOLOGIS SISWA SMA NEGERI 1 AYAH: DENGAN MODERASI MEDIA SOSIAL - Robi Mustika; Fandy Ahmad Yunian; Ridlo Kamaludin Hendardi; Retno Dwiyanti (Universitas Muhammadiyah Gresik, 2025)
Background: Academic stress is a factor that often reduces students' psychological well-being, especially in terms of their emotions and mental balance. Along with the development of technology, social media plays a significant role as a social interaction tool, but its excessive use can worsen the effects of academic stress. Objective: This study aims to identify the effect of academic stress on the psychological well-being of students of SMA Negeri 1 Ayah with the moderation of social media use. Method: This study used a quantitative method with a population of students of SMA Negeri 1 Ayah. The instruments used included an academic stress scale, a social media use scale, and a psychological well-being scale. Results: The study showed that social media use was a significant moderator in the relationship between academic stress and psychological well-being. Conclusion: In the low social media user group, the relationship between academic stress and psychological well-being was relatively weak (β = -0.17, R2 = 0.080) with only 8% of the variation in psychological well-being in this group explained by academic stress. Conversely, in the high social user group, this relationship was much stronger, namely (β = -0.47, R2 = 0.396), indicating that 39.6% of psychological well-being was influenced by academic stress.